AIDS and the Blood Supply: An Analysis of Law, Regulation, and Public Policy - Steven R. Salbu (Washington University Law Quarterly, 1996)
Acquired Immune Deficiency Syndrome ("AIDS") is among the greatest challenges to modem epidemiology. As the number of diagnosed cases and predicted future infections mounts, the need to stem the transmission of the Human Immunodeficiency Virus ("HIV") becomes an increasingly crucial public health issue. Since scientists first diagnosed AIDS and began to understand its viral source in the early 1980s, lawmakers and policymakers have sought responses to eliminate or retard the spread of HIV. As the quest for a vaccination or a cure has proven frustratingly elusive, managing AIDS in the short term has come to depend largely on measures that control its contagion. Some measures focus on reducing the instance of voluntary, high-risk activities, such as unsafe sexual practices and the sharing of hypodermic needles. Other measures attempt to lower the risk of unavoidable activities, such as blood transfusion. This Article focuses on the latter challenge—the development of laws, regulations, and policies to reduce the presence of HIV in the blood supply. Section II briefly discusses the problem of blood supply purity throughout the world. Section III distinguishes liability-based approaches from rule-based approaches to improving blood purity. Section IV examines and analyzes various rule-based options. Section V summarizes the recommendations made throughout the Article.
Keywords: AIDS (Disease); Blood banks; Cost effectiveness